1984
DOI: 10.1159/000166810
|View full text |Cite
|
Sign up to set email alerts
|

Crescentic Glomerulonephritis Associated with Nonrenal Malignancies

Abstract: A review of 80 patients with the renal biopsy diagnosis of idiopathic glomerulonephritis with extracapillary proliferation (crescentic GN) disclosed 7 cases with a coexistent nonrenal malignancy; 6 carcinomas and 1 lymphoma. In a control group of 80 patients with the renal biopsy diagnosis of minimal change or focal segmental glomerulosclerosis, only 1 case of coexistent malignancy was found (chi-square = 4.74, p < 0.05). All of the malignancies occurred in patients older than 40 years of age and the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…Since this report, numer ous studies have confirmed that membranous [7][8][9] but also membranoproliferative [10] and crescentic [11][12][13] glomeru lonephritis may be of paraneoplastic origin. Surgical tumor removal may be followed by regression of the nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 74%
“…Since this report, numer ous studies have confirmed that membranous [7][8][9] but also membranoproliferative [10] and crescentic [11][12][13] glomeru lonephritis may be of paraneoplastic origin. Surgical tumor removal may be followed by regression of the nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 74%
“…In our opinion extracapillary lesions, which have frequently been described, also deserve consideration: the relationship between crescentic glomerulonephritis and malignancies and the significance of this relation ship have been recently underlined [28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…In Drash's syndrome the hypothesis ol a common embryogenetic defect of the urogenital ridge has been supported [4,8,12,14]. It has been suggested [9,12,18], particularly in the absence of genital abnormalities, that an immunolog ical mechanism similar to that involved in glomerulone phritis associated with nonrenal tumors [10,[30][31][32][33] leads to deposits of immune complexes in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest an association between rapidly progressive GN and malignancies, with a prevalence of cancer between 7% and 9% (27,28). A variety of tumors have been described (10).…”
Section: Other Carcinoma-associated Glomerulopathiesmentioning
confidence: 99%